Assessment of the neuronal underpinnings of cognitive impairment in bipolar disorder with a picture encoding paradigm and methodological lessons learnt. (August 2021) - Petersen, JZ; Macoveanu, J; Kjærstad, HL; Knudsen, GM; Kessing, LV; Miskowiak, KW
Background: Mood disorders are often associated with persistent cognitive impairments. However, pro-cognitive treatments are essentially lacking. This is partially because of poor insight into the neurocircuitry abnormalities underlying these deficits and their change with illness progression. Aims: This functional magnetic resonance imaging (fMRI) study investigates the neuronal underpinnings of cognitive impairments and neuronal change after mood episodes in remitted patients with bipolar disorder (BD) using a hippocampus-based picture encoding paradigm. Methods: Remitted patients with BD ( n =153) and healthy controls ( n =52) were assessed with neuropsychological tests and underwent fMRI while performing a strategic picture encoding task. A subgroup of patients ( n =43) were rescanned after 16 months. We conducted data-driven hierarchical cluster analysis of patients' neuropsychological data and compared encoding-related neuronal activity between the resulting neurocognitive subgroups. For patients with follow-up data, effects of mood episodes were assessed by comparing encoding-related neuronal activity change in BD patients with and without episode(s). Results: Two neurocognitive subgroups were revealed: 91 patients displayed cognitive impairments while 62 patients were cognitively normal. No neuronal activity differences were observed between neurocognitive subgroups within the dorsal cognitive control network or hippocampus. However, exploratory whole-brain analysis revealed lower activity within a small region of middle temporal gyrus in impaired patients, which significantly correlated with poorer neuropsychological performance. No changes were observed in encoding-related neuronal activity or picture recall accuracy with the occurrence of mood episode(s) during the follow-up period. Conclusion: Memory encoding fMRI paradigms may not capture the neuronal underpinnings of cognitive impairment or effects of mood episodes.